Enteric-Coated Strategies in Colorectal Cancer Nanoparticle Drug Delivery System - Wathoni N; Nguyen AN; Rusdin A; Umar AK; Mohammed AFA; Motoyama K; Joni IM; Muchtaridi M (Dove Medical Press, 2020)
Nasrul Wathoni,1,2 An Ny Nguyen,3 Agus Rusdin,1 Abd Kakhar Umar,1 Ahmed Fouad Abdelwahab Mohammed,4 Keiichi Motoyama,5 I Made Joni,2,6 Muchtaridi Muchtaridi2,7 1Department of Pharmaceutics and Pharmaceutical Technology, Faculty of Pharmacy, Universitas Padjadjaran, Sumedang 45363, Indonesia; 2Functional Nano Powder University Research Center of Excellence, Universitas Padjadjaran, Sumedang 45363, Indonesia; 3Department of Pharmacy, Faculty for Chemistry and Pharmacy, Ludwig Maximilians Universität Munich, Germany; 4Department of Pharmaceutics, Faculty of Pharmacy, Minia University, Minia 61519, Egypt; 5Graduate School of Pharmaceutical Sciences, Kumamoto University, Kumamoto 862-0973, Japan; 6Department of Physics, Faculty of Mathematics and Natural Sciences, Universitas Padjadjaran, Sumedang 45363, Indonesia; 7Department of Pharmaceutical Analysis and Medicinal Chemistry, Universitas Padjadjaran, Sumedang 45363, IndonesiaCorrespondence: Nasrul WathoniDepartment of Pharmaceutics and Pharmaceutical Technology, Faculty of Pharmacy, Universitas Padjadjaran, Jatinangor 45363, IndonesiaTel +6222 842 888888Email nasrul@unpad.ac.idAbstract: Colorectal cancer is one of the most common cancer diseases with the increase of cases prevalence > 5% every year. Multidrug resistance mechanisms and non-localized therapy become primary problems of chemotherapy drugs for curing colorectal cancer disease. Therefore, the enteric-coated nanoparticle system has been studied and proved to be able to resolve those problems with good performance for colorectal cancer. The highlight of our review aims to summarize and discuss the enteric-coated nanoparticle drug delivery system specific for colorectal cancer disease. The main and supporting literatures were collected from published research articles of journals indexed in Scopus and PubMed databases. In the oral route of administration, Eudragit pH-sensitive copolymer as a coating agent prevents the degradation of the nanoparticle system from the gastric fluid and releases drug to intestinal-colon track. Therefore, it provides a colon-specific targeting ability. Impressively, enteric-coated nanoparticles having a sustained release profile significantly increase the cytotoxic effect of chemotherapeutic drugs and achieve cell-specific target delivery. The enteric-coated nanoparticle drug delivery system represents an excellent modification to improve the effectiveness and performance of anticancer drugs for colorectal cancer disease in terms of the oral route of administration.Keywords: drug delivery system, oral route, cytotoxic, anticancer drugs